Assessing the Quality of Financial Management Practices among Micro, Small, and Medium Enterprises in Makassar City - Nidrah Nidrah; Muhaidir Ikram (Jurnal Multidisiplin Sahombu, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an essential role in supporting local economic growth, employment creation, and business resilience in Indonesia. However, many MSMEs still face challenges in implementing systematic financial management practices, particularly in financial recording, budgeting, cash flow monitoring, and financial reporting. This study aims to describe the quality of financial management among MSMEs in Makassar City based on respondents’ answers. This research employed a descriptive quantitative approach involving 150 MSME actors as respondents. The population was categorized as unknown, and the sample was selected using non-probability sampling with a purposive sampling technique. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using descriptive statistics, including frequency, percentage, mean, and category interpretation. The findings indicate that the overall quality of financial management among MSMEs in Makassar City is in the good category, with an average score of 3.88. The strongest aspect is the separation of personal and business finances, while the weakest aspect is the preparation of simple income statements. These results show that MSME actors have developed basic financial discipline but still need improvement in structured financial reporting. The study implies that MSME development programs should strengthen practical bookkeeping, income statement preparation, cash flow analysis, and evidence-based financial decision-making to support business sustainability.